Al2O3-coated Li1.2Mn0.54Ni0.13Co0.13O2 nanotubes as cathode materials for high-performance lithium-ion batteries. Issue 4 (16th January 2019) - Chen, Yangwen; Wang, Xinchang; Zhang, Jiajia; Chen, Baiyuan; Xu, Junmin; Zhang, Sen; Zhang, Liwei
Abstract : Li-rich manganese-based layered cathode Li1.2 Mn0.54 Ni0.13 Co0.13 O2 (LMNCO) nanotubes are synthesized by electrospinning and surface coated with different amounts of amorphous Al2 O3 . Abstract : Li-rich manganese-based layered cathode Li1.2 Mn0.54 Ni0.13 Co0.13 O2 (LMNCO) nanotubes are synthesized by electrospinning and surface coated with different amounts of amorphous Al2 O3 . The effects of the coating content of Al2 O3 on the structural and electrochemical performances of LMNCO nanotubes are investigated systematically. The results show that the morphologies and structures of the samples exhibit no apparent changes after being coated with Al2 O3 . Electrochemical tests indicate that the Al2 O3 -coated LMNCO nanotubes exhibit obviously enhanced electrochemical performances. The initial coulombic efficiency of surface modified LMNCO nanotubes increased from 74.9% to 85.2%, and the modified LMNCO nanotubes have a high capacity retention of 97.6% after 90 cycles at 1C. The improved electrochemical performances of the coated samples are attributed to the protective function of the uniform Al2 O3 coating and the three-dimensional Li + diffusion channel in the spinel interface layer.